Development of Innovative Integrated Last Planner System (ILPS) - Aslam, Mughees; Gao, Zhili; Smith, Gary (International journal of civil engineering (Tehran. Online), 2020)
Last planner system (LPS) has been recognized as one of the most formidable tools for implementing lean construction (LC) and improving construction productivity. The past 25 years have witnessed the sequential development of LPS but still, the construction industry is unable to utilize its full potentials. It was reported that users of LPS were only able to achieve 70% of their weekly assignments with much potential to perform better. Considering it is a complete lean construction tool, LPS is mostly implemented in isolation, thereby exposing many areas that are overlooked and poorly managed. In this study, an effort has been made in developing strategies to overcome LPS implementation challenges by integrating LPS with other available lean tools and techniques. A systematic literature review is carried out, followed by a conceptual development of findings and theories into a robust integrated LPS implementation model. Thirteen (13) major shortcomings in implementing LPS and sixteen (16) lean tools to overcome these shortcomings are identified. Presently, LPS is managed as a single entity. However, due to its vast diversity, all of its stages should be managed independently. In this study, lean tools are integrated within LPS stages to develop the innovative integrated last planner system (ILPS), allowing the management of LPS stages independently. Additionally, a guideline for sequential amalgamation of LPS with the lean tools at different stages is presented to smoothen the ILPS implementation process. The ILPS will facilitate the construction industry in utilizing LPS to its fullest potential. This newly developed ILPS will help the lean practitioners in increasing construction productivity and reducing cost and time.